Descemetorhexis Without Endothelial Keratoplasty Versus DMEK for Treatment of Fuchs Endothelial Corneal Dystrophy. Issue 12 (December 2018) - Huang, Marshall J.; Kane, Steven; Dhaliwal, Deepinder K.
Abstract : Purpose: To compare the visual outcomes and associated morbidity of patients with Fuchs endothelial corneal dystrophy who were treated with either Descemet membrane endothelial keratoplasty (DMEK) or descemetorhexis without endothelial keratoplasty (DWEK). Methods: This is a retrospective comparative cohort study of 27 eyes with mild to moderate Fuchs dystrophy (with corneal guttae/edema limited to the central cornea with relatively clear periphery) that were treated at the University of Pittsburgh Medical Center from 2015 to 2017 with either DMEK (n = 15) or DWEK (n = 12). Descemetorhexis was performed by removing the central 4 mm of diseased Descemet membrane at the end of phacoemulsification for cataract surgery. Visual acuity was measured using the Snellen chart and then converted to logMAR for analysis. Results: Average postoperative pinhole visual acuity was 20/25 − 1 (logMAR 0.16 ± 0.09) for DMEK eyes and 20/30 + 1 (logMAR 0.13 ± 0.10) for DWEK eyes ( P = 0.44). The average time to 20/40 vision for DMEK was 2.2 ± 2.8 weeks compared with 7.1 ± 2.7 weeks for DWEK ( P < 0.01). In our DMEK group, 8 (53%) patients had adverse events, including increased intraocular pressure (n = 7), anterior chamber inflammation (n = 1), and graft nonadherence (n = 1), with 1 patient requiring anterior chamber paracentesis (6.7%) and 1 patient (6.7%) requiring a rebubbling procedure. Our DWEK group had no adverse events ( P < 0.01). Conclusions: DWEK effectively treats select patients with mild to moderate Fuchs dystrophy with equivalent visual outcomes compared with the current standard of care, DMEK. Although the recovery time may be longer, DWEK patients had reduced adverse events and need for additional procedures and did not require long-term immunosuppression or donor corneal tissue.